Impact of modified surface properties on photocatalytic activities of TiO2 for degradation of high polymers - SUN Zhen-shi; CHEN Ying-xu; FANG Si; YANG Ye (浙江大学学报. 农业与生命科学版, 2001)
Immoblized photocatalytic oxidation of polyvinyl alcohol (PVA) was investigated in an open fixed-bed photoreactor illuminated with 250W high pressure mercury lamp and using supported catalyst of TiO2, Pt/TiO2 or Fe3+/TiO2. The results showed that the catalyst of TiO2 which was with lwt% Pt by photochemical process had the most efficient photocatalytic activity. When Pt/TiO2 30 g/m2 were fixed on the bottom of the plannar photoreactor, the removal rate of PVA reached to 78.4% after 60 minutes illumination. It was also found that the overloaded Pt would decrease the photocatalytic activity of TiO2. However, the Fe3+/TiO2 prepared by a high-temperature sintering technique may mainly quench the creation of ·OH radicals. By contrast of series of SEM, it seemed that the photocatalytic activity of TiO2 was related closely with the ratio surface area of TiO2.